Analisis Penerapan Strategi Operasi dalam Kegiatan Produksi pada UMKM Johny Walker Leatherworks di Kota Cimahi Jawa Barat - Irawan, Andri (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2018)
In Indonesia, there are some cities that have relatively large number of MSMEs. One city that has a large percentage of MSMEs is Cimahi City in West Java Province Based on regional MSMEs mapping and product type, cluster of SMEs Cimahi City is divided into 4 parts, namely food and beverage clusters, fashion cluster, cluster craft and information technology cluster. UMKM Johnny Walker Leatherworks is one type of business engaged in the field of handmade located at Jalan Kihapit No. 84 Leuwigajah Village, South Cimahi Sub-district, Cimahi City. The purpose of research has been done is to see how far the implementation of an operating strategy in the production activities of a UMKM. The type of research used is qualitative research. Technique of taking data is done by using observation and interview. Based on the discussion that has been done results obtained as follows that the operation strategy that has been done by UMKM Johny walker Leatherworks has a positive impact but as an evaluation of the implementation of the strategy is that UMKM Johny Walker Leatherworks MSME should start designing the right operating strategy to reach Cimahi City market Keywords: Operation Strategy